Liquidity and leverage on the financial performance of savings and credit cooperatives in the emerging Thailand market - Pojanavatee, Sasipa; Kingshott, Russel (Emerald, 2025)
Purpose The purpose of this study is to examine the impact of liquidity, leverage and debt-to-equity (DE) ratio on the profitability of police savings and credit cooperatives (PSCC) within the emerging Thailand market.